Pulmonary nodules in a patient with rheumatoid arthritis: Which diagnostic approach is the most appropiate? - Ines Mahmoud; Aicha Ben Tekaya; Rawdha Tekaya; Olfa Saidane; Leila Gafsi; Mathilde Benhammou; Fautrel Bruno (Babol University of Medical Sciences, 2017)
Background: Pulmonary nodular excavation should firstly evoke tuberculosis or necrosis broncho-pulmonary tumor, particularly: epidermoid carcinoma. The case discussed here illustrated these difficulties in patients with rheumatoid arthritis (RA). Case Presentation: A 63-year-old woman was presented with a-three-year history of RA and a recent discovery of an excavated pulmonary nodule. Initial investigations focused on a rheumatoid origin. The evolution of the disease was worrisome and surgical exploration was deemed mandatory. The result was the discovery of a nodule of a malignant nature. Conclusion: In this paper, we discussed the excavation of the pulmonary nodule, its diagnoses and management of the difficulties we encountered.